2017
DOI: 10.1128/jvi.00805-17
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Serine 225 in Hepatitis C Virus NS5A Regulates Protein-Protein Interactions

Abstract: Hepatitis C virus (HCV) nonstructural protein 5A (NS5A) is a phosphoprotein that plays key, yet poorly defined, roles in both virus genome replication and virion assembly/release. It has been proposed that differential phosphorylation could act as a switch to regulate the various functions of NS5A; however, the mechanistic details of the role of this posttranslational modification in the virus life cycle remain obscure. We previously reported (D. Ross-Thriepland, J. Mankouri, and M. Harris, J Virol 89:3123–313… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 56 publications
2
37
1
1
Order By: Relevance
“…We also used confocal microscopy with Airyscan to analyse the distribution of both total NS5A and pS225-NS5A in cells infected with the various phosphoablatant mutants. As shown in Fig 6, all mutants displayed a broad cytoplasmic distribution of total NS5A that was similar to wildtype, with the exception of S225A which exhibited a more compact perinuclear distribution, as documented previously (23). However, as observed in Fig 1, we noted again that in all cases there was a subset of total NS5A reactivity that did not stain for pS225, and this led us to investigate this observation in more detail.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…We also used confocal microscopy with Airyscan to analyse the distribution of both total NS5A and pS225-NS5A in cells infected with the various phosphoablatant mutants. As shown in Fig 6, all mutants displayed a broad cytoplasmic distribution of total NS5A that was similar to wildtype, with the exception of S225A which exhibited a more compact perinuclear distribution, as documented previously (23). However, as observed in Fig 1, we noted again that in all cases there was a subset of total NS5A reactivity that did not stain for pS225, and this led us to investigate this observation in more detail.…”
Section: Resultssupporting
confidence: 84%
“…We previously demonstrated a role for S225 phosphorylation in HCV genome replication, and further showed that this was likely mediated via interactions of NS5A with a defined subset of cellular factors (23, 37). A caveat to these studies was the necessary dependence on interpretation of data based on the analysis of the phenotype of S225 mutants (S225A phosphoablatant or S225D phosphomimetic).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations